The Al-Assad Regime: Social Media and Visual Culture in Syria - Chaparro-Medina, Martha Carolina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The Syrian conflict has been mediated through social media, shaping visual narratives that influence both domestic dynamics and international perceptions. Bashar Al-Assad's regime, opposition groups, and external powers leverage these platforms to construct ideological narratives, disseminate propaganda, and mobilize global audiences. Using the Paris School's focus on semiotics and culture, this study explores how images and videos construct representations of power, violence, and resistance. From the Toronto School's perspective, social media redefines the public sphere and decentralizes information in a post-truth era. Social media thus serves a dual role: enabling resistance while reinforcing narrative control, shaping a "visual culture of conflict."